Determination Parameters of a Hybridvehicle in Its Life Cycle - Volodarets, Mykyta; Kletska, Olha; Hatchenko, Viktoriia; Shuleshko, Dmitriy; Kosariev, Oleg (International Journal of Engineering and Technology, 2018)
This work considered methods of selection of power plant and energy storage of hybrid vehicle. An analysis has been performed and its shortcomings are indicated. A generalized scheme to define optimal technical and economic indexes of hybrid vehicle is drawn up and adapted for shunting locomotive. A model was created on its base with appropriate restrictions, which takes into account the shortcomings of existing models. Parameters of different types of hybrid locomotives based on diesel locomotives series ChME3 were defined, depending on type of operation. Comparative traction characteristics of shunting locomotive series ChMe3 and diesel locomotive with hybrid transmission on the its base were built. Relevant calculations were fulfilled using these characteristics. Â